Probe-free allele-specific copy number detection and analysis of tumors - Zhu, Ailin; Guan, Xiaowei; Gu, Xinbin; Xie, Guiqin (Analytical biochemistry, 2016)
Cancer development and progression frequently involve nucleotide mutations as well as amplifications and deletions of genomic segments. Quantification of allele-specific copy number is an important step in characterizing tumor genomes for precision medicine. Despite advances in approaches to high-throughput genomic DNA analysis, inexpensive and simple methods for analyzing complex nucleotide and copy number variants are still needed. Real-time polymerase chain reaction (PCR) methods for discovering and genotyping single nucleotide polymorphisms are becoming increasingly important in genetic analysis. In this study, we describe a simple, single-tube, probe-free method that combines SYBR Green I-based quantitative real-time PCR and quantitative melting curve analysis both to detect specific nucleotide variants and to quantify allele-specific copy number variants of tumors. The approach is based on the quantification of the targets of interest and the relative abundance of two alleles in a single tube. The specificity, sensitivity, and utility of the assay were demonstrated in detecting allele-specific copy number changes critical for carcinogenesis and therapeutic intervention. Our approach would be useful for allele-specific copy number analysis or precise genotyping.